2015
DOI: 10.1002/jmrs.127
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns of radiation therapy technology in Australia: results of a national audit

Abstract: IntroductionThis article presents the results of a single‐day census of radiation therapy (RT) treatment and technology use in Australia. The primary aim of the study was to ascertain patterns of RT practice and technology in use across Australia. These data were primarily collated to inform curriculum development of academic programs, thereby ensuring that training is matched to workforce patterns of practice.MethodsThe study design was a census method with all 59 RT centres in Australia being invited to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…Our results show that all NZ centres had IMRT/VMAT capabilities, in keeping with international trends reporting increased adoption of these techniques over time. 10,12 We found a high uptake of IMRT/ VMAT in H&N and GU malignancies and selective use in other sites, similar to the trend reported in an Australian survey. 10 The strong utilization of IMRT/VMAT for H&N and GU sites is supported by the literature, with improved outcomes in these patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results show that all NZ centres had IMRT/VMAT capabilities, in keeping with international trends reporting increased adoption of these techniques over time. 10,12 We found a high uptake of IMRT/ VMAT in H&N and GU malignancies and selective use in other sites, similar to the trend reported in an Australian survey. 10 The strong utilization of IMRT/VMAT for H&N and GU sites is supported by the literature, with improved outcomes in these patients.…”
Section: Discussionsupporting
confidence: 85%
“…There was a broad range of number of staff members per centre for ROs (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), physicists (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and radiation therapists .…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…identified portal imaging as the most common modality for image guidance. A previous Australian audit conducted in 2012 in Queensland found that MV EPI was still the dominant imaging modality compared with planar kV and CBCT, and in 2013 the same authors demonstrated the increasing use of kV CBCT . The trend of in‐room IGRT uptake followed the changes in technology for in‐room IGRT techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A previous Australian audit conducted in 2012 in Queensland found that MV EPI was still the dominant imaging modality compared with planar kV and CBCT, 14 and in 2013 the same authors demonstrated the increasing use of kV CBCT. 15 The trend of in-room IGRT uptake followed the changes in technology for in-room IGRT techniques. The use of non-ionising radiation-based imaging systems is increasing and is often used in conjunction with radiation-based systems.…”
Section: Discussionmentioning
confidence: 99%